Música y su influencia en el desarrollo de la conciencia fonológica en estudiantes de 4 a 5 años de Educación Inicial de la Unidad Educativa Francisco Huerta Rendón - Gómez Flores, Thalia Ibeth (2023)
Music is a very present tool in the education of children, because it is a didactic resource that helps to stimulate various factors in learning. Phonological awareness, understood as the ability to recognize the phonological structure of spoken language and segment it into its constituent units, is recognized as a key precursor to reading acquisition. That said, in the present case study entitled "Music and its influence on the development of Phonological Awareness in Students from 4 to 5 years of Early Education of the Francisco Huerta Rendon Educational Unit" the objective of this research is to analyze how music influences the development of phonological awareness. There is evidence that musical activities in the initial level and in the first years of school, strengthen the auditory discrimination of rhythmic and melodic elements, in such a way that children's linguistic skills are favored, particularly the skills that make up phonological awareness.